Mitigating Strawberry Generation Risks Through Multiple Learning Strategies in Kindergarten - Apriyansyah, Chandra; Sukatmi, Sri; Mustafa, Lily Muliana (Jurnal Pendidikan Anak, 2023)
The efforts made by early childhood education teachers to address the risks associated with "Strawberry Generation" qualities are the subject of this study. The study aims to investigate the methods teachers use to counteract the detrimental impacts of these traits and encourage young children's development of good character. Data were gathered through interviews and observations using the qualitative research method. A sample of early childhood education teachers actively tackling the Strawberry Generation phenomena participated in the study. The study's conclusions point to several efficient tactics educators employ to counter the risks posed by Strawberry Generation features. These tactics include encouraging active student participation, using active learning techniques, acting as positive role models, storytelling and narratives, working with parents, and using active learning methodologies. With the help of these techniques, educators can help kids comprehend the drawbacks of Strawberry Generation features and encourage the development of good character traits as alternatives. The study emphasizes how crucial parent-teacher cooperation is in overcoming the difficulties brought on by Strawberry Generation features. The results highlight the importance of regular efforts, communication, and support from parents and teachers in assisting children in developing desirable character traits. This study adds to the corpus of knowledge by shedding light on early childhood educators' role in mitigating the risks associated with Strawberry Generation features. The findings have practical ramifications for educators, parents, and governments interested in early childhood education. Early childhood education teachers can be crucial in fostering children's excellent character characteristics and mitigating the harmful effects of the Strawberry Generation phenomena by using appropriate tactics.